2015
DOI: 10.1021/acs.jnatprod.5b00357
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Homoisoflavones from the Bulbs of Bellevalia eigii

Abstract: Eight new and 10 known compounds, were isolated from an organic extract of the bulbs of Bellevalia eigii as part of a search for anticancer leads from native plants of Jordan. Of these, the series of 16 homoisoflavonoids (1-16), comprise the seven new analogues 7-O-methyl-3′-hydroxy-3,9-dihydropunctatin (3), 6-hydroxy-7-O-methyl-3,9-dihydropunctatin (6), 7,4′-di-O-methyl-3′-hydroxy-3,9-dihydropunctatin (9), 7-O-methylpunctatin (10), 7-O-methyl-3′-hydroxypunctatin (13), 5-hydroxy-7,8-dimethoxychroman-4-one (14)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…The structures of all the newly synthesized compounds were characterized by IR, 1 H NMR, 13 C NMR spectroscopies, and CHN analyses. It is well‐known that the geometry of compounds is affected by thermodynamically controlled reactions . So at room temperature and even by rising temperature up to 80°C, E isomer is obtained, while in the presence of hυ irradiation conditions, Z isomer is formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The structures of all the newly synthesized compounds were characterized by IR, 1 H NMR, 13 C NMR spectroscopies, and CHN analyses. It is well‐known that the geometry of compounds is affected by thermodynamically controlled reactions . So at room temperature and even by rising temperature up to 80°C, E isomer is obtained, while in the presence of hυ irradiation conditions, Z isomer is formed.…”
Section: Resultsmentioning
confidence: 99%
“…So at room temperature and even by rising temperature up to 80°C, E isomer is obtained, while in the presence of hυ irradiation conditions, Z isomer is formed. Therefore, the molecular configuration of all of the compounds that have been obtained at room temperature is assigned as E configuration …”
Section: Resultsmentioning
confidence: 99%
“…The ROESY correlations of H-5/H-8 β , H-7/H-8 α , Me-12/H-5, Me-15/H-6, and H-6/H-1 indicated the α -orientations of H-1, H-6, and H-7 and the β -orientations of H-4 and H-5. The absolute configuration was determined by application of the Snatzke’s helicity rule1013141516. The P/M -helicity of the dihydropyran ring in FPMs controlled the signs of Cotton effects approximately between 270–310 nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cytotoxic effect of homoisoflavonoids has been indicated elsewhere, 12) and the structureactivity relationship has been investigated. 13) Accordingly, the 2′-hydroxy and 4′-methoxy groups seem to have a contribution to the activity. In our study, compounds 1, 2, and 3 possessing 2′-hydroxy and 4′-methoxy substituent showed positive effect on at least one cancer cell line.…”
Section: )mentioning
confidence: 94%